What We're About Out Here: The Resilience and Relevance of School Farms in Rural Tasmania - Michael Corbett; Peter Brett; Charlie-Lynn Hawkins (Journal of Research in Rural Education, 2017)
School farms were established in Tasmania in the 1930s following a visit of an Australian eduation offi cial to the United States and the United Kingdom. There are still more than 30 school farm operations functioning in some capacity throughout the state, unlike in the rest of Australia where similar small school farms are not common. In this article we analyze interviews undertaken in 2016 with 22 school farm educators about the state of Tasmania's school farms, what they do, how they are seen in their communities, what challenges they face, and how they integrate the agricultural program with the demands of contemporary curriculum. While these school farms face considerable challenges, we conclude that they have a unique place in the state's education system, a powerful symbolic presence in rural communities, and signifi cant potential to provide relevant, valuable, and potentially transformative curriculum and pedagogy in support of educational and rural development policy agendas.